Case Study : Jaman Tory Resepi / Mohd Faiz Fikri Mohammad Johar - Mohammad Johar, Mohd Faiz Fikri (2020)
This case study actually helps to expose the student to the real world of the entrepreneurship. Therefore, by doing this project student should be able to learn a lot of new things in the world of business. As a student, they should be able to identify the problems that the businessman has to face in order to be successful in business. In the real world, to be a successful businessman they should start from the bottom so that they will learn to be a better person. As the former British Prime Minister said, “Success is walking from failure to failure with no loss of enthusiasm”. Case study also helps students to understand on how to calculate the net profit, know how to identify the business opportunity, threat, weakness and strength and also how to overcome the business problems.